(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the level of YKL-40 and fibronectin in patients with total placenta previa and to evaluate the presence of placental invasion anomaly such as accreta. Materials and Methods: A total of 60 patients were included in this prospective study. The patients were classified according to the placental localization as assessed through ultrasound. The study group consisted of 33 patients diagnosed with placenta previa or accreta with previous cesarean section. These patients were also subdivided into two groups according to the histopathological examination results as invasion-positive group and invasion-negative group. The control group consisted of 27 patients who were admitted to the gynecology clinic with previous cesarean deliveries and had normal placental localization. Serum YKL-40 and fibronectin levels were measured in two groups via human chitinase-3-like protein 1 (Ykl-40/CHI3L1) and fibronectin enzyme-linked immunosorbent assay kits. Results: Mean serum levels for YKL-40 and fibronectin were similar between the study and control groups. In the subgroup analysis according to invasion anomaly, the level of YKL-40 in invasion-positive group (n=11) was higher than invasion-negative group (n=22), indicating a statistically significant difference. Conclusion: Outcomes of this research indicates that YKL-40 can be used as a marker for identifying placental invasion anomalies.